Greedy Based Radio Resource Allocation Algorithm with Water Filling Power Control Scheme in D2D Underlaying Communication - Rezha Aulia Riyanda; Nachwan Mufti Adriansyah; Vinsensius Sigit Widhi Prabowo (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2021)
Device to Device (D2D) is communication between two devices directly without the intervention of eNodeB.This communication can improve sum-rate, spectral efficiency, and decrease the workload of eNodeBbecause this communication uses the same spectrum frequency with Cellular User Equipment (CUE).D2D pair use the same resource simultaneously with CUE to communicate, this communication is calledD2D underlaying communication. D2D and CUE use the same resource and cause interference. Thisinterference should be managed by a resource allocation algorithm. In this work, the resource is allocatedin a single cell and the communication is from CUE to eNodeB which is called uplink communication. Thejoint greedy algorithm with water filling power control scheme is used as a resource allocation algorithmin this work. This algorithm is compared with the greedy, joint greedy, and greedy algorithm with a waterfilling power control scheme. The joint greedy algorithm works based on the capacity of eNodeB and D2Dpair. While water filling power control is used to manage the power of each user based on the channelcondition. After all of the resource is allocated, the parameter performance of the system such as spectralefficiency, energy efficiency, and D2D fairness are calculated. The simulation result that joint greedyalgorithm with water filling power control scheme obtains 29,34 bps/Hz in spectral efficiency, 0.939 x 10 7bps/watt in energy efficiency, and 0,996 in D2D fairness.